On low-velocity impact response of foam-core sandwich panels. (1st September 2020) - Huo, Xintao; Liu, Hao; Luo, Quantian; Sun, Guangyong; Li, Qing
Highlights: Theoretical model of the impact strength prediction for foam sandwiches under different impactors. FE model for penetration response of foam sandwiches under impact load. Mechanism analysis of impact-resistance enhancement based on experimental results. Energy absorbing mechanism analysis and structural optimization based on the FE model. Abstract: This study aimed to investigate low-velocity impact responses and crashworthiness of different aluminum foam-core sandwich structures. Several drop-weight dynamic impact tests were first conducted on both sandwich structures and their individual components to explore the mechanism of energy absorption and interactive effect between the foam core and facesheets. Different shapes and sizes of impactors were used in the experiments. The full-field deflection distribution was acquired by a 3D optical scanner to assess the failure patterns. A full-scale finite element model was then created to simulate the low-velocity impacting response of the foam-core sandwich panels. After the finite element model was validated against the experimental results, it was used to further explore the crash behavior of multi-layered sandwiches. It was found that multi-layer sandwich structure had much better performance in the crush force efficiency than those with single-layer foam core. Based upon the energy principle, an energy-based analytical model was also derived to estimate the initial peak load. It was demonstrated that the analytical predictions were in good agreement with the experimental and numerical results. The presented experimental, numerical and analytical studies are anticipated to provide systematic understanding and new knowledge for design of multilayer sandwich configurations aiming at more desirable impact resistance and better lightweight characteristics. Graphical abstract: Image, graphical abstract